Spatiotemporal Zones of Neosomnambulism - Tony D. Sampson (Media Theory, 2020)
Drawing on Deleuze and Guattari’s (1994) methodology developed in their swansong, What is Philosophy?, this article deploys its own conceptual persona: the Neosomnambulist or new sleepwalker. Not to be mistaken for an actual living person, the Neosomnambulist is utilized so as to bring concepts to life. In this case, what the sleepwalker gives life to are spatiotemporal zones of indistinction that pervade the digital now.